ANALISIS MARKETING MIX TERHADAP KEPUASAN PELANGGAN PROVIDER XL DI JAKARTA UTARA - Cyntia Clara Sirait (2021)
This study aims to analyze the effect of product variables, price, place, promotion, process, and physical evidence on customer satisfaction of XL providers in North Jakarta. The method used is quantitative with descriptive analysis techniques followed by inferential analysis techniques using SmartPLS tools. This population collection is taken from customers who have used or are currently using XL providers in North Jakarta. Sampling using non probability sampling. Sources of data obtained through the results of distributing questionnaires as many as 100 respondents. The results obtained are (1) product has no significant effect on customer satisfaction, (2) price has a significant effect on customer satisfaction, (3) promotion does not have a significant effect on customer satisfaction, (4) place has a significant effect on customer satisfaction (5) people who have a significant effect on customer satisfaction, (6) process has no significant effect on customer satisfaction, (7) physical evidence does not have a significant effect on customer satisfaction. The limitation of this research is due to the pandemic. The distribution uses the G-Form so that it is less close to the respondents.